Clostridium difficile infection and inflammatory bowel disease - Cojocariu, Camelia; Stanciu, Carol; Stoica, Oana; Singeap, Ana Maria; Sfarti, Catalin; Girleanu, Irina; Trifan, Anca (Turkish Journal of Gastroenterology, 2014)
Abstract Over the past 15 years, Clostridium difficile infection (CDI) in patients with inflammatory bowel disease (IBD) has increased both in incidence and severity. Traditional risk factors for CDI are similar in IBD and non-IBD populations, but there is a significant proportion of IBD patients which have distinctive characteristics. Patients with ulcerative colitis (UC) are more susceptible to CDI and have more severe outcomes than those with Crohn’s disease (CD). CDI may be difficult to distinguish from an IBD flare due to similar clinical presentation, and therefore screening for CDI is recommended at every flare in such patients. Several studies showed worse clinical outcomes in IBD patients with CDI, including longer hospital stay, higher colectomy and mortality rates than in those without CDI. Vancomycin and metronidazole appear to have similar efficacy in patients with moderate disease, but vancomycin is preferred in severe disease. Measures must be taken to prevent the spread of infection. Clinicians should have a high index of suspicion for CDI when evaluating a patient with IBD flare, as rapid detection and prompt treatment of infection improve outcomes. This review summarizes the available literature on epidemiology, risk factors, clinical aspects, diagnostic methods, treatment, outcome, and prevention of CDI in IBD patients.